The P2X7 receptor in activated microglia promotes depression- and anxiety-like behaviors in lithium -pilocarpine induced epileptic rats. (September 2020) - Hong, Sun; Xin, Yu; JiaWen, Wu; ShuQin, Zhan; GuiLian, Zhang; HaiQin, Wu; Zhen, Gao; HongWei, Reng; YongNan, Li
Abstract: Depressive and anxious behaviors are the most common psychiatric symptoms of epilepsy, and may aggravate the epileptic condition and affect the patient's quality of life. Accumulating data obtained from both experimental animal models and patients have convincingly shown a critical role of P2X7 receptor (P2X7R) during depression and anxiety. Our study showed for the first time that the P2X7R is involved in promoting depression- and anxiety-like behaviors in lithium pilocarpine-induced epileptic rats. More importantly, direct anti-depressive and anti-anxiety effects were produced by the P2X7R antagonist Brilliant Blue G (BBG) is in this study, and the effect was similar to that of the classic anti-depressant and anti-anxiety drug fluoxetine. We also found that BBG did not affect the development of spontaneous recurrent seizures (SRS) and had a neuroprotective effect via inhibition of microglial activation after status epilepticus (SE). Thus, our data provide evidence that the P2X7R in activated microglia promotes depression- and anxiety-like behaviors in lithium-pilocarpine induced epileptic rats. Since previous studies have indicated that some anti-depression and anti-anxiety drugs may exacerbate seizures, our data support that the P2X7R is a promising therapeutic target for epilepsy associated with depression and anxiety. Highlights: Depression- and anxiety-like behaviors were notably increased in epileptic rats. P2X7R expression was increased by enhanced microglial activation after SE. BBG treatment alleviated depressive- and anxiety-like behavior in epileptic rats. P2X7R may be a useful therapeutic target for epilepsy associated with depression and anxiety.